Early antithrombotic post-discharge therapy using prophylactic DOAC or dipyridamole improves long-term survival and cardiovascular outcomes in hospitalized COVID-19 survivors - Motloch, Lukas J.; Jirak, Peter; Mirna, Moritz; Fiedler, Lukas; Davtyan, Paruir A.; Lakman, Irina A.; Gareeva, Diana F.; Tyurin, Anton V.; Gumerov, Ruslan M.; Matskeplishvili, Simon T.; Pavlov, Valentin N.; Cai, Benzhi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Cardiovascular events are common in COVID-19. While the use of anticoagulation during hospitalization has been established in current guidelines, recommendations regarding antithrombotic therapy in the post-discharge period are conflicting. Methods To investigate this issue, we conducted a retrospective follow-up (393 ± 87 days) of 1,746 consecutive patients, hospitalized with and surviving COVID-19 pneumonia at a single tertiary medical center between April and December 2020. Survivors received either 30-day post-discharge antithrombotic treatment regime using prophylactic direct oral anticoagulation (DOAC; n = 1,002) or dipyridamole (n = 304), or, no post-discharge antithrombotic treatment (Ctrl; n = 440). All-cause mortality, as well as cardiovascular mortality (CVM) and further cardiovascular outcomes (CVO) resulting in hospitalization due to pulmonary embolism (PE), myocardial infarction (MI) and stroke were investigated during the follow-up period. Results While no major bleeding events occured during follow-up in the treatment groups, Ctrl showed a high but evenly distributed rate all-cause mortality. All-cause mortality (CVM) was attenuated by prophylactic DOAC (0.6%, P < 0.001) and dipyridamole (0.7%, P < 0.001). This effect was also evident for both therapies after propensity score analyses using weighted binary logistic regression [DOAC: B = −3.33 (0.60), P < 0.001 and dipyridamole: B = −3.04 (0.76), P < 0.001]. While both treatment groups displayed a reduced rate of CVM [DOAC: B = −2.69 (0.74), P < 0.001 and dipyridamole: B = −17.95 (0.37), P < 0.001], the effect in the DOAC group was driven by reduction of both PE [B−3.12 (1.42), P = 0.012] and stroke [B = −3.08 (1.23), P = 0.028]. Dipyridamole significantly reduced rates of PE alone [B = −17.05 (1.01), P < 0.001]. Conclusion Late cardiovascular events and all-cause mortality were high in the year following hospitalization for COVID-19. Application of prophylactic DOAC or dipyridamole in the early post-discharge period improved mid- and long-term CVO and all-cause mortality in COVID-19 survivors.